Adapted Physical Educators’ Social Media Usage for Professional Learning - McNamara, Scott; Ng, Kwok; Healy, Sean (Frontiers in Education, 2022)
Physical educators report a multitude of benefits from accessing informal learning opportunities via social media. However, a lack of research has been conducted on adapted physical education (APE) teachers’ usage of social media for professional learning (PL) purposes. Thus, the purpose of this study was to explore how APE teachers use social media to learn about APE content. A survey was used to identify APE teachers’ (n = 73) social media usage patterns. Descriptive statistics were reported, and multiple t-tests were used to compare how participants perceived the usefulness of social media versus conferences for PL purposes. Multiple linear regression analyses were also used to identify variables that predicted the participants’ likelihood of attending conferences and using social media for PL purposes. Results demonstrated many participants used an array of social media platforms to learn about topics such as activities and equipment. However, participants indicated that conferences were significantly more useful in gaining information about APE related topics compared to social media. Following multivariate analysis, personal and professional usage of social media for PL purposes was associated with conference attendance. The potential of APE teachers and organizing bodies to use social media for PL purposes and future research recommendations are discussed.